Font Size: Small Medium Large Economic Sector Portfolio Optimization in the Commercial and Retail Segments - Sulistyorini, Diah Diana; Hartoyo, Sri; Andati, Trias (UI Scholars Hub, 2016)
Credit disbursement is an investment decision in the banking business. Therefore, the concept of